Knowledge of AIDS and HIV risk-related sexual behavior among Nigerian naval personnel - Ajuwon Ademola J; Nwokoji Ugboga (BMC, 2004)
Abstract Background The epidemic of HIV continues to grow in Nigeria. Personnel in the military are at increased risk of HIV infection. Although HIV-risk related sexual behavior of Nigerian police officers has been studied, little is known about the sexual behavior of their counterparts in the Navy. This study describes knowledge of AIDS, and HIV-risk sexual behavior of naval personnel in Lagos Nigeria. Methods Four hundred and eighty personnel of the Nigerian Navy completed a 70-item questionnaire in 2002. Group discussion and in-depth interviews of four key informants were also conducted to gain insights into the context of risky sexual behaviors and suggestions for feasible HIV primary prevention interventions. Results The mean age of the respondents was 34 years. Although the overall mean AIDS knowledge score was 7.1 of 10 points, 52.1% of respondents believed that a cure for AIDS was available in Nigeria and that one can get HIV by sharing personal items with an infected person (25.3%). The majority (88.1%) had had lifetime multiple partners ranging from 1-40 with a mean of 5.1; 32.5% of male respondents had had sexual contact with a female sex worker, 19.9% did so during the six months preceding the survey. Forty-one percent of those with sexual contact with a female sex worker did not use a condom during the most recent sexual encounter with these women. Naval personnel who have been transferred abroad reported significantly more risky sexual behaviors than others. Group discussants and key informants believed that sex with multiple partners is a tradition that has persisted in the navy even in the era of AIDS because of the belief that AIDS affects only foreigners, that use of traditional medicine provides protection against HIV infection, and influence of alcohol. Conclusion Many naval personnel report participating in high-risk sexual behavior which may increase their risk of acquiring and spreading HIV. Naval personnel live and interact freely with civilian population and are potential bridging group for disseminating HIV into the larger population. Interventions including sustained educational program, promotion of condoms, changes in transfer policies are recommended to address this problem.